Dynamic cervical lung lobe herniation in a Shih Tzu dog - T. S. Y., Joanne; Lim, M. L.; Asnawi, O.; Shamsul, M. A. H.; Khor, Kuan Hua (Veterinary Association Malaysia, 2019)
An 8-year-old spayed female Shih Tzu was referred to University Veterinary Hospital (UVH) with history of chronic coughing for more than a year duration. Dry, hacking cough was heard and bilateral wheezing lung sound was noted upon physical examination. Auscultation of heart revealed left apical systolic heart murmur Grade III/VI. A soft, intermittent swelling was observed at ventral neck, cranial to thoracic inlet (protruded upon expiration and collapsed upon inspiration). Thoracic radiography taken showed presence of apical radiolucency at cervical region and bronchial pattern at caudodorsal lungs with left atrium enlargement and right-sided heart enlargement. Echocardiographic examination revealed myxomatous mitral valve disease (MMVD) with mild regurgitation. Based on diagnostic imaging, this case was diagnosed as dynamic lung lobe herniation secondary to chronic coughing concurrent with myxomatous mitral valve disease. Other differential diagnosis that may lead to chronic cough such as of tracheal collapsed and bronchiectasis was not rule out.